Development and Challenges in Copper-Catalyzed Asymmetric Ullmann-Type Coupling Reactions - Cai, Qian; Zhou, Fengtao (Synlett, 2013)
Ullmann-type coupling is one of the most powerful methods for the formation of aryl C–C, C–N, and C–O bonds. Yet asymmetric Ullmann coupling has received little attention because of the great challenges in both ligand and reaction designs. The success of the first catalytic enantioselective intramolecular Ullmann C–N coupling reaction through an asymmetric desymmetrization strategy offers a new way to develop enantioselective variants of such reactions. This paper addresses the importance of the desymmetrization strategy in Ullmann-type couplings and outlines some future directions in this field.
Keywords: copper catalysis; asymmetric desymmetrization; Ullmann coupling; enantioselectivity; indolines